2022
DOI: 10.1001/jamaneurol.2022.1634
|View full text |Cite|
|
Sign up to set email alerts
|

Association of APOE Genotypes and Chronic Traumatic Encephalopathy

Abstract: ImportanceRepetitive head impact (RHI) exposure is the chief risk factor for chronic traumatic encephalopathy (CTE). However, the occurrence and severity of CTE varies widely among those with similar RHI exposure. Limited evidence suggests that the APOEε4 allele may confer risk for CTE, but previous studies were small with limited scope.ObjectiveTo test the association between APOE genotype and CTE neuropathology and related endophenotypes.Design, Setting, and ParticipantsThis cross-sectional genetic associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 51 publications
(110 reference statements)
0
16
0
Order By: Relevance
“…Adopting a multidisciplinary approach while treating patients with CTE is important. Sports medicine doctors and other physicians/licensed health professionals caring for athletes participating in contact sports as well as other people at risk for repeat head injury should begin thinking about ways to limit head trauma and minimize the risk for CTE long before the onset of the disease [3,[33][34][35][64][65][66][67]103]. In patients who go on to develop the disease, a variety of health care professionals may be helpful in managing the diverse symptoms and coordinating the supportive care needed by each individual patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting a multidisciplinary approach while treating patients with CTE is important. Sports medicine doctors and other physicians/licensed health professionals caring for athletes participating in contact sports as well as other people at risk for repeat head injury should begin thinking about ways to limit head trauma and minimize the risk for CTE long before the onset of the disease [3,[33][34][35][64][65][66][67]103]. In patients who go on to develop the disease, a variety of health care professionals may be helpful in managing the diverse symptoms and coordinating the supportive care needed by each individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Players and coaches should be counseled on the importance of following these guidelines [33,34]. Although repeat head injuries are the primary risk factor for CTE, other risk factors such as genetics, comorbidities, lifestyle, and psychosocial factors may also modulate a person's risk of disease development [3,35,[64][65][66][67]. The APOEε4 allele may be associated with worsened CTE pathology on autopsy and is suspected to worsen outcomes and recovery after TBI [35,68].…”
Section: Treatmentsmentioning
confidence: 99%
“…White matter is under strong genetic control, with complex polygenic influences that impact the normal microstructure of axons, myelin, and oligodendrocytes, an individual's susceptibility to a variety of brain diseases, and responses to centrally-acting medications ( 110 ). In the clinic, it has been known since the 1990s that the apolipoprotein E ε4 (APOE 4 ) allele is a risk factor for AD ( 111 ), and recent findings suggest that this variant may also increase the risk of CTE ( 112 ). Moreover, new evidence has suggested that a substantial component of WMH may be related to genetic factors ( 113 ), helping explain why adults with little or no vascular risk, and without migraine, may have notable WMH on MRI.…”
Section: Future Directionsmentioning
confidence: 99%
“…Validation of fluid biomarkers is still an area of active investigation and current clinical trials are determining the proteomic and transcriptomic profiles associated with CTE [NCT04928534]. Additionally, genetic markers, including APOEε4 and TMEM106B may also be useful for diagnosing CTE, specifically for establishing links between genetic predispositions and CTE [118,119]. However, pathophysiologic, and genetic biomarkers alone do not possess adequate power for definitively diagnosing CTE.…”
Section: Pathophysiological and Genetic Biomarkersmentioning
confidence: 99%